JOURNALISTIC NARRATIVES ABOUT THE “DAY OF FIRE”: a Luso-Brazilian perspective on the Amazon - Braga, Thaís Luciana Correa; Marinho, Sandra (Brazilian journalism research, 2023)
ABSTRACT – The “day of fire” in the Amazon refers to forest fires allegedly caused by farmers in the state of Pará, Brazil, in 2019. This article aims to identify and understand the strategies for constructing journalistic narratives about this event. Folha de S.Paulo (Brazil) and Público (Portugal) were the newspapers selected for the observation and analysis of the case. As data collection techniques/tools, an analysis grid was used (direct observation), and semi-structured interviews with journalists involved in the case coverage (indirect observation). The pragmatic analysis of the journalistic narrative was applied to the discoursive analysis. The results show that, in the Brazilian newspaper, the conflict was structured with a beginning, middle, and end, and produced the sense that environmental crimes in the Amazon remain unpunished. In the Portuguese newspaper, the conflict ended in anticlimax and created the feeling that it was necessary to save the Amazon for the next generations. RESUMO – O “dia do fogo” na Amazônia refere-se aos incêndios florestais alegadamente provocados por agropecuaristas do Estado do Pará, no Brasil, em 2019. Neste artigo pretende-se identificar e compreender as estratégias de construção das narrativas jornalísticas sobre este acontecimento. Foram selecionados os jornais Folha de S.Paulo (Brasil) e Público (Portugal) para a observação e análise do caso. Como técnicas/instrumentos de recolha dos dados, recorreu-se a uma grelha de análise (observação direta) e entrevistas semiestruturadas com jornalistas envolvidos na cobertura do caso (observação indireta). Para a análise discursiva, operacionalizou-se a análise pragmática da narrativa jornalística. Os resultados revelam que, no jornal brasileiro, o conflito foi estruturado com começo, meio e fim, bem como produziu o sentido de que os crimes ambientais na Amazônia ficam impunes. Já no jornal português, o conflito terminou em anticlímax e produziu o sentido de que é preciso salvar a Amazônia para as próximas gerações. RESUMEN – El “día del fuego” en la Amazonía se refiere a los incendios forestales supuestamente provocados por agricultores en el estado de Pará, Brasil, en 2019. Este artículo tiene como objetivo identificar y comprender las estrategias para construir narrativas periodísticas sobre este evento. Folha de S.Paulo (Brasil) y Público (Portugal) fueron los periódicos seleccionados para la observación y análisis del caso. Como técnicas/herramientas de recolección de datos se utilizó una matriz de análisis (observación directa) y entrevistas semiestructuradas a periodistas involucrados en la cobertura del caso (observación indirecta). El análisis pragmático de la narrativa periodística se aplicó al análisis discursivo. Los resultados muestran que, en el diario brasileño, el conflicto se estructuró con un principio, un medio y un final, y produjo la sensación de que los crímenes ambientales en la Amazonía quedan impunes. En el diario portugués, el conflicto terminó en anticlímax y creó la sensación de que era necesario salvar la Amazonía para las próximas generaciones.